Dimensi Policy Network dalam Pengembangan Kawasan Minapolitan di Kecamatan XIII Koto Kampar, Provinsi Riau - Lubis, Ema Fitri; Sujianto; Febri Yuliani; Auradian Marta (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2025)
This study aims to analyze the implementation of the Minapolitan area development policy in Koto Mesjid Village, XIII Koto Kampar, Riau Province, through a policy network approach. The method used is descriptive qualitative with data collection techniques in the form of observation, in-depth interviews, documentation, and questionnaires. The results show that the Minapolitan policy involves actors from various sectors: government, community, private sector, NGOs, and academics. This study uses Van Waarden's seven dimensions to examine policy networks, including: actors, which include individuals and groups with an interest in the policy-making process. The second indicator concerns the role of actors in the policy network. The third indicator, structure, examines the patterns of relationships between the actors involved. The fourth indicator, institutionalization, is assessed as the organizing institution or organization. The fifth indicator, rules of behavior, concerns the procedural and behavioral constraints on actors. The sixth indicator, power relations, is related to collaboration in actor interactions, and the seventh indicator, actor strategies, refers to the methods used to achieve goals. The findings show that even though a collaborative network has been formed, there are still obstacles in terms of unequal power distribution, a lack of cross-sectoral network institutionalization, and a low level of understanding of technical policy rules at the local level. This study concludes that in order to achieve the goals of integrated and sustainable Minapolitan area development, it is necessary to strengthen institutional synergy, increase the capacity of local actors, and restructure policy networks in an inclusive manner.